How does job insecurity relate to self‐reported job performance? Analysing curvilinear associations in a longitudinal sample. Issue 4 (28th May 2013) - Selenko, Eva; Mäkikangas, Anne; Mauno, Saija; Kinnunen, Ulla
<x xml:space="preserve">Abstract</x> The study focuses on the relationship between job insecurity and self‐reported job performance. Based on theoretical, empirical, and statistical arguments, we propose that this relationship is U‐shaped and mediated by vigour at work. This assumption was tested cross‐sectionally and across two measurement points, and against two alternative explanations, namely that the U‐shaped relationship might be due to the influence of the moderators optimism and supervisory support. The findings of a study among a large group of job‐insecure employees of two Finish universities (n = 2, 095) confirm the U‐shaped effect of job insecurity on self‐reported job performance. This effect was shown to be robust against the moderating influence of optimism and supervisory support and was partially explained by decreased vigour. The inclusion of a second data wave indicated that job insecurity predicted job performance 1 year later also in a U‐shaped form (n = 1, 289). Overall, the results suggest that taking quadratic effects into account adds to the understanding of the relationship between job insecurity and self‐reported job performance. Practitioner points The study reveals that the relationship between job insecurity, vigour, and self‐reported performance is slightly U‐shaped. At lower to moderate degrees of intensity, job insecurity is negatively related to self‐reported job performance, whereas at higher degrees, the effect is less negative. The U‐shaped effect can partly be explained by vigour: at low and high degrees of job insecurity, vigour is slightly less impaired than at moderate degrees. The study does not indicate that job insecurity is a motivator in the workplace.